2018
DOI: 10.1007/s00203-018-1595-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the genome of Arctic Psychrobacter sp. DAB_AL32B and construction of novel Psychrobacter-specific cloning vectors of an increased carrying capacity

Abstract: Cold-active bacteria are currently of great interest in biotechnology, and their genomic and physiological features have been extensively studied. One of the model psychrotolerant bacteria are Psychrobacter spp. Analysis of Arctic psychrophilic Psychrobacter sp. DAB_AL32B genome content provided an insight into its overall stress response, and genes conferring protection against various life-limiting factors (i.e., low temperature, increased ultraviolet radiation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 63 publications
(75 reference statements)
0
13
0
Order By: Relevance
“…The available draft genomic data for Psychrobacter sp. DAB_AL32B [22] was insufficient to permit the assembly of the complete nucleotide sequence of plasmid pP32BP2. Therefore, plasmid DNA was isolated and sequenced de novo using Illumina technology.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The available draft genomic data for Psychrobacter sp. DAB_AL32B [22] was insufficient to permit the assembly of the complete nucleotide sequence of plasmid pP32BP2. Therefore, plasmid DNA was isolated and sequenced de novo using Illumina technology.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, plasmid DNA was isolated and sequenced de novo using Illumina technology. An analysis of the assembled sequence revealed that the size of pP32BP2 is 54,438 bp, with an average GC content of 39.9%, which is lower than that of the DAB_AL32B chromosome (41.9%) [22], but similar to the average value for other Psychrobacter plasmids (39.2%) (GenBank). The manual annotation of the pP32BP2 sequence identified 54 genes, which constitute 77.9% of the plasmid genome.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations